2011
DOI: 10.1177/0145445511427193
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Brief Acceptance and Commitment Therapy for Psychosis

Abstract: A previous report explored the impact of a brief (four session) acceptance and commitment therapy (ACT) intervention as compared with treatment as usual (TAU) on rehospitalization over 4 months in a sample of 80 inpatients with psychosis. The present study extended the follow-up period to 1 year and used a more sophisticated survival analysis to take previous hospitalization and length of the current hospitalization into account. Those in the ACT condition showed reduced hospitalization as compared to those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 26 publications
1
55
0
4
Order By: Relevance
“…Bach and Hayes (2002) found in a sample of 80 inpatients reporting hallucinations or delusional beliefs that a brief 4-session intervention reduced rehospitalization over 4 months post-discharge compared to a treatment-as-usual (TAU) control condition; differences were maintained 1 year post release (Bach, Hayes, & Gallop, 2012). Gaudiano and Herbert (2006) replicated this study with controls for therapist contact.…”
mentioning
confidence: 60%
“…Bach and Hayes (2002) found in a sample of 80 inpatients reporting hallucinations or delusional beliefs that a brief 4-session intervention reduced rehospitalization over 4 months post-discharge compared to a treatment-as-usual (TAU) control condition; differences were maintained 1 year post release (Bach, Hayes, & Gallop, 2012). Gaudiano and Herbert (2006) replicated this study with controls for therapist contact.…”
mentioning
confidence: 60%
“…ACT also encourages individuals to clarify their personal values and engage in behaviors that are consistent with these values in order to help them regulate their emotions. Randomized controlled trials have found that in adults ACT decreases: depression (Öst, 2014), psychotic symptoms (Bach and Hayes, 2002;Bach, Hayes, and Gallop, 2012;Gaudiano and Herbert, 2006;White et al, 2011), panic disorder, generalized anxiety disorder, and social anxiety (Arch et al, 2012;Avdagic, Morrissey, and Boschen, 2014), obsessive-compulsive disorder (Twohig et al, 2010), drug and nicotine dependence (Hernández-López, Luciano, Bricker, Roales-Nieto, and Montesinos, 2009;Luoma, Kohlenberg, Hayes, and Fletcher, 2012), borderline personality disorder (Gratz and Gunderson, 2006;Morton, Snowdon, Gopold, and Guymer, 2012), chronic pain (Hann and McCracken, 2014;Veehof, Oskam, Schreurs, and Bohlmeijer, 2011;Weineland, Arvidsson, Kakoulidis, and Dahl, 2012;Wetherell et al, 2011), and improves weight control (Forman et al, 2007;Juarascio, Forman, and Herbert, 2010;Lillis, Hayes, Bunting, and Masuda, 2009). Research evidence for the application of ACT with adolescents is less extensive although four randomized controlled trials have found that it can reduce depressive symptoms, unsafe sexual behaviors, chronic pain, anxiety, and stress (Hayes, Boyd, and Sewell, 2011;Livheim et al, 2014;Metzler, Biglan, Noell, Ary, and Ochs, 2000;Wicksell, Melin, Lekander, and Olsson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Da zahlreiche Studien die Relevanz von Emotionsregulation im Zusammenhang mit Wahnerleben nachweisen konnten [Westermann et al, 2013;Perry et al, 2011], wäre eine Erweiterung von CBT-p um aktivere Komponenten der Emotionsregulation sinnvoll. Hierzu könnten das Erkennen von emotionalen Zuständen (achtsamkeitsbasierte Interventionen als wirksame Verfahren [Khoury et al, 2013]) sowie die Akzeptanz wiederkehrender Symptome und belastender emotionaler Prozesse zählen, wie sie derzeit in Studien zu Negativsymptomatik und Depressivität [White et al, 2011] sowie zur stationären Akutbehandlung und Prävention von Rehospitalisierung [Bach et al, 2012] …”
Section: Kritische Einordnung Der Ergebnisseunclassified